Breathing Exercise untuk Meningkatkan Fungsi Respirasi pada Pasien Pasca Pembedahan Abdomen - Rizki Paramita Sakti; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effective breathing exercise technique on respiratory function in post-abdominal surgery patients. This research design is a literature study using the search engines Science Direct, EBSCO, Wiley Online, and Clinical Key. The results showed similarities in the interventions applied, namely breathing exercises with various techniques such as deep breathing exercise, coughing activity, balloon blowing exercise, pursed lip exercise, diaphragm breathing exercise, inspiratory muscle exercise, and incentive spirometer volume and flow control exercise. The intervention was performed with a duration of 10 minutes within five days preoperatively and postoperatively. In conclusion, preoperative breathing exercises can improve lung function performance and reduce the risk of postoperative pulmonary complications. Keywords: Breathing Exercise, Respiratory Function, Post Abdominal Surgery